Prenatal exposure to modafinil alters locomotor behaviour and leucocyte phagocytosis in mice - Ruda-Kucerova, Jana; Amchova, Petra; Machalova, Alena; Pistovcakova, Jana; Sulcova, Alexandra (Psychiatria Danubina, 2018)
BACKGROUND: Modafinil is a psychostimulant drug prescribed mainly for treatment of narcolepsy but is used as a "smart drug" by wide populations to increase wakefulness, concentration and overall mental performance. The aim of this study was to assess potential developmental toxicity of modafinil. MATERIALS AND METHODS: Pregnant female mice were given either saline or modafinil (50 mg/kg orally) from gestational day (GD) 3 to GD 10 and then a challenge dose on the GD 17. The male offspring were treated analogously at the age of 10 weeks. Changes in the spontaneous locomotor/exploratory behaviour and anxiogenic profile in the open-field test were assessed in naive animals, after an acute and 8th modafinil dose and the challenge dose following a 7-day wash-out period. One month after completion of the behavioural study, the leukocyte phagocytosis was examined by zymosan induced and luminol-aided chemiluminiscence assay in vitro. RESULTS: The most important finding of this study was the immunosuppressing effect on leukocyte activity, hypolocomotion and increased behavioural response to modafinil-induced psychostimulation caused by prenatal exposure to the same drug. We did not detect significantly altered anxiety-related behaviour in any group disregarding the pre- and postnatal treatments. CONCLUSION: This is the first evidence of developmental toxicity of modafinil which needs to be taken into account as a potential risk factor when modafinil is administered to women who may become or are pregnant.
Keywords: Luminol; gestační stáří; Animals; luminiscenční měření; Female; Age Factors; Gestational Age; ženské pohlaví; modafinil; věkové faktory; Mice; těhotenství; Locomotion; zpožděný efekt prenatální expozice; myši; leukocyty; Modafinil; lokomoce; Male; modely nemocí na zvířatech; fagocytóza; Leukocytes; Mice, Inbred ICR; Phagocytosis; Disease Models, Animal; Prenatal Exposure Delayed Effects; myši inbrední ICR; zvířata; mužské pohlaví; Pregnancy; luminol; Luminescent Measurements